Experimental Study of an SWH System with V-Shaped Plate - Jalaluddin, Jalaluddin; Arif, Effendy; Tarakka, Rustan (Journal of Engineering and Technological Sciences, 2016)
Solar energy is known as an environmentally friendly energy source with a wide range of applications. This energy can be utilized in various applications such as domestic and industrial water heating using solar water heating (SWH) systems. The thermal performance of an SWH system using a V-shaped absorber plate is presented in this study. Two SWH systems with different absorber plates, i.e. a flat-plate and a V-shaped plate, have been investigated experimentally. First, the absorptivity of the absorber plates was calculated analytically. The optimum V-shaped configuration with angle at Î² = 21Â° (V-shaped dimensions t = 4 cm and l = 4 cm) was determined from various V-shaped plate absorbers based on their absorptivity and applied in the experimental study. Two SWH systems were installed and tested at a low flowrate of 0.5 L/min and at a high flowrate of 2 L/min. The results showed that the SWH system with V-shaped plate absorber had a 3.6-4.4% better performance compared with that of the system with flat-plate absorber.